1971
DOI: 10.1128/iai.3.6.849-850.1971
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Carbohydrates on Hemolysin Production by Escherichia coli

Abstract: The production of hemolysin by Escherichia coli after adding various carbohydrates to starved cultures was investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1984
1984
1985
1985

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Others found that AH is produced in CDM in the absence of a medium meat factor (5-7, 78,94). Production of AH in CDM was first described by Snyder and Koch (94).…”
Section: Physiological Aspectsmentioning
confidence: 99%
“…Others found that AH is produced in CDM in the absence of a medium meat factor (5-7, 78,94). Production of AH in CDM was first described by Snyder and Koch (94).…”
Section: Physiological Aspectsmentioning
confidence: 99%